Barriers and facilitators of follow-up among women with precancerous lesions of the cervix in Cameroon: a qualitative pilot study - Manga S; Kiyang E; DeMarco RF (Dove Medical Press, 2019)
Simon Manga,1,2 Edith Kiyang,1 Rosanna F DeMarco2 1Women’s Health Program, Cameroon Baptist Convention Health Services, Bamenda, Cameroon; 2College of Nursing and Health Sciences, University of Massachusetts Boston, Boston, MA, USA Purpose: This pilot study explores the barriers to adherence to follow-up among women with cervical precancer in urban Cameroon. While follow-up of women with a positive screening of cervical precancer is the most important aspect of cervical cancer secondary prevention, women with cervical precancer do not adhere frequently to recommended follow-up schedule in Cameroon. The aim of the study was to explore and describe the barriers and facilitators to follow-up for cervical precancer among women infected and uninfected with HIV in Cameroon. Participants and methods: A qualitative research design was used to answer the research questions. Participants included eight HIV-infected and -uninfected women diagnosed with cervical precancer and 19 nurses. Data were collected by in-depth individual patient interviews and focus groups with nurses. An interview guide with open-ended questions, using the social ecological model as a framework, included questions that addressed the complexities of the lives of individuals and professionals within a relational context. The interviews were audio-taped and transcribed verbatim in English language. Thematic analysis of data was completed with no epistemological or theoretical perspective underpinning the analyses. Results: Four major themes emerged from the study. They were clinic, personal, and social barriers, and strategies to improve follow-up. Conclusion: The use of reminder phone calls and fee reduction, coupled with peer counseling and navigation of women who have been diagnosed with cervical precancer, could be effective ways of improving adherence to follow-up. Further research is needed to explore the same phenomenon among women in rural areas, especially those who were initially attended to in mobile clinics. Keywords: cervical precancer, follow-up, HIV-infected women, HIV-uninfected women